2019
DOI: 10.1177/2047487319890973
|View full text |Cite
|
Sign up to set email alerts
|

Screening young athletes for diseases at risk of sudden cardiac death: role of stress testing for ventricular arrhythmias

Abstract: Aims: The athletic preparticipation evaluation (PPE) protocol proposed by the European Society of Cardiology includes history, physical examination and resting electrocardiogram (ECG). The aim of this study was to assess the results of adding constant-load ECG stress testing (EST) to the protocol for the evaluation of ventricular arrhythmias (VA) inducibility. Methods: We evaluated a consecutive cohort of young athletes with history, physical examination, resting ECG and EST. Athletes with VA induced by EST un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 34 publications
2
31
0
5
Order By: Relevance
“…Some papers applied the genetic test in the diagnostic flow-chart of cohorts of athletes targeted for the evidence of ECG anomalies with/without clinical symptoms. These studies unveiled that the percentage of genotype-positive athletes is significant and contributes as an integrative diagnostic instrument in athletes selected on the basis of a strong clinical suspicion for inherited cardiac disease [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 49 , 50 ]. Indeed, Cronin et al demonstrated that, in a small cohort of athletes (N: 10), the evidence of TWI at ECG without a clinical phenotype was not related to a specific genetic background [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some papers applied the genetic test in the diagnostic flow-chart of cohorts of athletes targeted for the evidence of ECG anomalies with/without clinical symptoms. These studies unveiled that the percentage of genotype-positive athletes is significant and contributes as an integrative diagnostic instrument in athletes selected on the basis of a strong clinical suspicion for inherited cardiac disease [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 49 , 50 ]. Indeed, Cronin et al demonstrated that, in a small cohort of athletes (N: 10), the evidence of TWI at ECG without a clinical phenotype was not related to a specific genetic background [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five studies carried out a genetic test on athlete populations, including white and black, elite and amateur athletes [ 45 , 46 , 47 , 48 , 49 , 50 ]. Among these, we excluded the study of Macarie et al [ 45 ], as the authors performed the genetic test using Multiple Ligation Dependent Probe Amplification (MLPA), exclusively, and did not precisely report the mutations found in the athletes.…”
Section: Diagnostic Yield Of Genetic Testing In Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In this issue of the journal, Alessandro Zorzi and colleagues 5 added an interesting piece of evidence by studying EST in predominantly adolescent athletes with a prospective follow-up. The novelty in that study is an advanced imaging strategy, using cardiac magnetic resonance imaging (CMR) in athletes with complex VA. 5 The authors enrolled 10,985 consecutive non-professional athletes (median age 15 years) undergoing annual PPE. In the total cohort, 9% of the athletes had abnormal findings, 4% were detected with medical history, physical examination or resting ECG alone and another 5% only during EST.…”
mentioning
confidence: 99%
“…8 In the United Kingdom regional registry, 26% of deceased athletes with non-ischaemic LV scar had died at rest, highlighting other potential triggers than exercise for life-threatening VA. 10 What are the clinical implications of the study by Zorzi et al? 5 The answer may be different from an Italian and European perspective. Within the framework of the distinct Italian sports law, criteria have been established to disqualify athletes at risk from competitive sports.…”
mentioning
confidence: 99%